Mapping High School Students' Critical Thinking in Biodiversity Learning through Problem-Based Learning and Structured Worksheets - Rikardus Herak (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This study aimed to explore and describe how the implementation of Problem-Based Learning (PBL), supported by structured student worksheets, facilitated high school students’ critical thinking during biodiversity learning, particularly in identifying problems, analyzing information, evaluating evidence, formulating arguments, and drawing conclusions. The participants were 66 Grade X students from a senior high school in Flores, East Nusa Tenggara, Indonesia. Data were collected during eight classroom meetings and analyzed through indicator-based coding, thematic interpretation, item-level descriptive analysis, and cross-source triangulation. The findings showed that 14 of 20 critical-thinking indicators, or 70%, were consistently observed during the PBL process, especially indicators related to connecting ideas, considering perspectives, distinguishing facts from opinions, evaluating consequences, constructing logical arguments, reflecting on thinking processes, validating information, and proposing solutions. Students' questionnaire responses were positive, ranging from 83.3% to 90.9%, with an average positive response of 88.0%. However, six indicators still required stronger teacher scaffolding, particularly those related to formulating clear problems, collecting relevant information independently, asking relevant questions, evaluating arguments, providing deeper explanations, and developing creative solutions. This study contributes classroom-based evidence by clarifying the alignment among PBL stages, worksheet prompts, and critical-thinking indicators. The findings imply that should be supported by explicit guidance, evidence-based questioning, argumentation prompts, and reflective assessment.